The Effect of Reciting Holy Qur’an toward Short-term Memory Ability Analysed trought the Changing Brain Wave - Very Julianto; Magda Bhinnety Etsem (Jurnal Psikologi, 2011)
The present study examined the effect of reciting Holy Qur’an toward short-term memory ability appearance from the change of the brain wave. Subjects of this study were four female students (n=4) from Gadjah Mada University with homogeneity of genders, age, thefrequencies of reciting Holy Qur’an, menstruation’s phase, timbre and ethnic groups. Subjects were divided randomly into two groups, i.e. experiment and control group. Each group wasrecorded with electroencephalograph (EEG) on their brain wave. The process of recording used monopolar method with placement of electrode 10-20 and the researcher give a free recall test.Either recording or free recall test is carried out twice, before and after execution and placebo. T-test result in experiment group from free recall test found significant are differences (t=-15,00; p<0.05) between before and after reciting the Holy Qur’an. T-test result in control group found that significantly not differences (t=-11,00; p>0,05) between before and afterplacebo effect. Hypotheses accepted i.e. there is significantly increasing in experiment group, before and after the execution. After the execution brain wave increased significantly in pointFp1, point Fp2 and point P4. In point Fp1,  ,  , and  significantly increased. In point Fp2, all of the wave significantly increased. In point P4, the wave increased were  ,  , and δ. Itmeans that when reciting Holy Qur’an, showed there is increased activity like thinking, emotionally and religion-related-activity or God.